2014
DOI: 10.1186/preaccept-2141223140138383
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the ex vivo virulence of Leishmania infantum isolates from Phlebotomus perniciosus from an outbreak of human leishmaniosis in Madrid, Spain

Abstract: Our data indicate that L. infantum isolates captured from this endemic area exhibited high virulence in terms of infection index, cytokine production and enzymatic activities involved in the pathogenesis of visceral leishmaniosis. Altogether, these data provide a starting point for the study of the virulence behaviour of parasites (BOS1FL1 and POL2FL7) isolated from P. perniciosus during the outbreak of human leishmaniosis in Madrid, Spain, and their involvement in infecting immunocompetent hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…More recently, research groups have used in vitro macrophage infection as an advantageous alternative in infectivity studies ( 17 , 18 , 28 ). Our previous experiments to standardize the in vitro conditions of macrophage and parasite co-cultures demonstrated that incubation after 3, 24, and 48 h resulted in consistent macrophage integrity and parasite growth (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, research groups have used in vitro macrophage infection as an advantageous alternative in infectivity studies ( 17 , 18 , 28 ). Our previous experiments to standardize the in vitro conditions of macrophage and parasite co-cultures demonstrated that incubation after 3, 24, and 48 h resulted in consistent macrophage integrity and parasite growth (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Cunha et al ( 17 ) characterized the biology and infectivity of viscerotropic and dermatotropic strains of L. infantum isolated from HIV+ and HIV- patients in the VL murine model, and demonstrated that in vivo and in vitro virulence are intrinsic characteristics of each strain. Another study that evaluated the ex vivo virulence of the L. infantum isolated from Phlebotomus perniciosus captured in an endemic area of Madrid, Spain, demonstrated that L. infantum strains exhibited high virulence, and were associated with cytokine production and enzymatic activities involved in the VL pathogenesis ( 18 ). Moreover, it has been shown that in vitro infection of human monocytes by Leishmania strains induced distinct immunological characteristics and the host cell's ability to control Leishmania ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, no specific tropism has been assigned to this ITS genotype. Recently, virulence of L. infantum isolates from P. perniciosus captured in the focus area was highlighted using an ex vivo model [ 59 ]. These authors showed that BOS1FL1 and POL2FL7 isolates displayed high virulence in terms of infection rates of murine macrophages and dendritic cells, cytokine production and enzymatic activities, undermining host immune defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the Mediterranean region, and in Central and South America, the disease is zoonotic and caused by L. infantum (= L. chagasi ) where the main reservoir is dogs (11). Recently, cats and leporids have also been considered as possible alternative reservoirs of VL in certain foci in the Mediterranean region (12). Ninety percent of VL cases occur in five countries – India, Bangladesh, Nepal, Sudan, and Brazil – most often in remote regions without ready access to medical care.…”
Section: Introductionmentioning
confidence: 99%